Translation and Validation of Computer Vision Syndrome Scale 17 (CVSS 17) – The Malay Version - Md-Yasin, Mazapuspavina; Din, Nor Shazatul Salwana; Tharek, Zahirah; Abd Aziz, Nor Azimah; Mohamad, Mariam (IIUM Medical Journal Malaysia, 2022)
Introduction: Computer Vision Syndrome Scale 17 (CVSS17) is a questionnaire to measure computer-related visual and ocular symptoms among video display terminal workers. This study aimed to translate CVSS17 into Malay languag and determine its psychometric properties among video display terminal workers. Materials and Methods: This was a cross-sectional validation study involving 206 workers in Universiti Teknologi MARA UiTM Selayang and Sungai Buloh Campus. The English version of the CVSS17 questionnaire is a 17-item scale measuring two key factors, which are internal symptom factors (11 items) and external symptom factors (6 items). The CVSS17 underwent forward-backward translation, face validation, and field testing to produce the Malay version. Validity of the items assessing psychometric properties was performed using exploratory factor analysis. The reliability testing was performed using internal consistency and test-retest reliability. Results: The validated CVSS17-Malay version retained all 17 items with acceptable factor loadings. There were 13 items in the external, and 4 items in the internal symptom factors domain. In comparison to the original version, 4 items (A2, A22, A28, A30) were swapped from internal to external symptom factors and 2 items (C16 and C23) swapped from external to internal symptom factors. The changes of these items into different domains were discussed. The overall Cronbach’s α was 0.867 and the intraclass correlation coefficient was 0.866. The Kaiser-Meyer-Olkin was 0.928, and Bartlett’s test of sphericity was p-value <0.001. Conclusion: The CVSS17 Malay version is valid, reliable, and stable over time, to be used in measuring computer vision syndrome among Malay-speaking workers.